2018
DOI: 10.1371/journal.pntd.0006452
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling for biomarkers in Schistosoma haematobium infection and associated bladder pathologies

Abstract: BackgroundMetabolic fingerprinting analysis can offer insights into underlying reactions in a biological system; hence it is crucial to the understanding of disease pathogenesis and could provide useful tools for discovering biomarkers. We sought to examine the urine and plasma metabolome in individuals affected by urogenital schistosomiasis and its associated-bladder pathologies.MethodologyBlood and midstream urine were obtained from volunteers who matched our inclusion criteria among residents from Eggua, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
1
19
1
Order By: Relevance
“…The majority of glycerophospholipids were significantly reduced in response to the infection, such as PC, phosphatidylethanolamine (PE), phosphatidylserine, phosphatidylinositol, and LysoPC. However, the concentration of some PCs was elevated in S. japonicum -infected mice, which was different from the results in S. haematobium -infected patients, where high levels of PC and PE were found ( 70 ). It is believed that the abundance of PC and PE in bladder endothelial cells may be one of the mechanisms for inducing cancer in chronic urogenital schistosomiasis ( 70 ); nevertheless, the different variations presented in PC after S. japonicum infection remain unclear, and future studies should address this question.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The majority of glycerophospholipids were significantly reduced in response to the infection, such as PC, phosphatidylethanolamine (PE), phosphatidylserine, phosphatidylinositol, and LysoPC. However, the concentration of some PCs was elevated in S. japonicum -infected mice, which was different from the results in S. haematobium -infected patients, where high levels of PC and PE were found ( 70 ). It is believed that the abundance of PC and PE in bladder endothelial cells may be one of the mechanisms for inducing cancer in chronic urogenital schistosomiasis ( 70 ); nevertheless, the different variations presented in PC after S. japonicum infection remain unclear, and future studies should address this question.…”
Section: Discussioncontrasting
confidence: 92%
“…Pathway analysis illuminated that both sphingolipid metabolism and glycerophospholipid metabolism were altered in the process of schistosomiasis, which is consistent with an earlier study of S. haematobium ( 70 ). In fact, sphingolipids and their derivatives have recently presented as promising drug targets for controlling infectious and inflammatory disease; however, how sphingolipid-mediated pathologies and how the host modifies sphingolipid metabolism to benefit itself remain unclear, and a better understanding of these mechanisms may provide new insights into new therapeutic strategies ( 83 ).…”
Section: Discussionsupporting
confidence: 89%
“…A modified phosphatidylcholine was also a potential target for an ATP carrier protein (Table 3). This may make biological sense as we previously reported that changes in phosphatidylcholine metabolism was a hallmark of schistosomiasis (Adebayo et al, 2018). The nutraceutical elements are also interesting as they are cheaply available if they do have any benefits.…”
Section: Potential Therapeutic Targetsmentioning
confidence: 88%
“…Other types of omics applications, such as genomics, epigenomics, transcriptomics and metabolomics, were also applied to determine biomarkers of bladder schistosomiasis. Metabolomic profiling using urine and plasma samples revealed that the perturbed glycerophospholipid and sphingolipid metabolisms are associated with schistosomiasis and its associated-bladder cancer pathologies [18]. Epigenetic regulation on RASSF1A and TIMP3 were found using a quantitative methylation-specific PCR assay in urine sediments of patients with schistosomiasis infection.…”
Section: Multi-omics Application For Bladder Bio-marker Developmentmentioning
confidence: 99%